Pengaruh Fee Based Income dan Giro Wajib Minimum terhadap Profitabilitas Bank Umum Syariah di Indonesia Periode 2018-2023 - Muthia Rivani; Nini Sumarni (Lembaga Pengembangan Kinerja Dosen, 2026)
This research is motivated by the importance of profitability in the Islamic banking industry in Indonesia, especially amidst increasingly tight competition and global economic challenges. Fee Based Income and Minimum Reserves are two factors that are considered to influence bank profitability. Therefore, the purpose of this study is to determine and analyze how much influence Fee Based Income and Minimum Reserves have on Net Profit Margin (NPM) in Islamic Commercial Banks in Indonesia during the period 2018-2023. This type of research is quantitative research with a descriptive analysis approach. The data used are secondary data accessed through the annual financial reports of banks registered with the Financial Services Authority (OJK). The sampling method used purposive sampling, and a sample of six banks was obtained with a total of 36 sample data. Data analysis techniques used include descriptive statistical analysis, classical assumption test, multiple linear regression analysis, determination coefficient test, and hypothesis test processed using the IBM SPSS 25 application. The results of the study indicate that partially, Fee Based Income has no significant effect on NPM with a significance value of 0.052≥ 0.05, and Minimum Reserves also have no significant effect with a significance value of 0.440≥ 0.05. In addition, the results of the F test indicate that both independent variables simultaneously have no significant effect on NPM, with a significance value of 0.117≥ 0.05. This indicates that although both variables have an important role, they are not strong enough to simultaneously affect bank profitability.